PENERAPAN PENDEKATAN SISTEM DALAM PERENCANAAN PENDIDIKAN ISLAM - Umam, Chotibul; Budiansyah; Romlah; Syaiful Anwar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The application of a systems approach in Islamic education planning significantly enhances the effectiveness and efficiency of the educational process. By focusing on essential components such as goals, inputs, processes, outputs, and evaluations, this approach ensures that all educational elements work synergistically to achieve Islamic educational objectives. This approach emphasizes the formation of students' character in line with Islamic values, making the process accountable and responsive to field needs. Furthermore, it optimizes resources by providing continuous evaluation, allowing improvements to align education with modern challenges. However, several challenges arise in implementing this approach, such as resistance from stakeholders, limited resources, and the need for teacher training. Addressing these challenges requires strategic steps like training programs, innovative resource management, and enhanced communication among stakeholders. With consistent support and commitment, the systems approach can drive Islamic education towards quality, efficiency, and accountability, shaping students with strong moral values and the skills society expects.